The protective role of green spaces in mitigating myopia prevalence - Guy Barnett-Itzhaki; Guy Barnett-Itzhaki; Zohar Barnett-Itzhaki; Daphna Mezad-Koursh; Daphna Mezad-Koursh (Frontiers Media S.A., 2024)
Near-sightedness, or myopia, is becoming more prevalent worldwide, but its etiopathogenesis is not fully understood. This review examines the potential protective role of green spaces in reducing myopia prevalence among children and adolescents, based on recent epidemiological studies from various countries. The studies consistently used the Normalized Difference Vegetation Index (NDVI) to quantify green space exposure. The analysis reveals a significant inverse relationship between exposure to green space and the risk of developing myopia, across multiple studies. For example, a 0.1 increase in NDVI within various buffer zones around schools was associated with a 6.3-8.7% reduction in myopia prevalence. Higher residential greenness within a 100-meter buffer around homes was linked to a 38% reduction in the risk of developing myopia among preschool children. The protective effect was observed across different age groups, from preschoolers to high school students. Urban planning factors, such as the size, connectivity, and aggregation of green spaces, also influenced myopia risk. These findings suggest that increasing access to green spaces in urban environments may be an effective strategy for myopia prevention, with important implications for public health and urban planning policies.